2023
DOI: 10.1109/access.2023.3253668
|View full text |Cite
|
Sign up to set email alerts
|

Very High Accuracy Hyperbolic Tangent Function Implementation in FPGAs

Abstract: The paper presents in detail a relatively simple implementation method of the hyperbolic tangent function, particularly targeted for FPGAs. The research goal of the proposed method was to examine the usage of the approximation of ordinary or Chebyshev polynomials for the implementation of the function. Several miscellaneous implementation versions have been considered. They differ in the polynomial degree, number of intervals for which the domain of the function is divided, etc. Both floatingpoint and fixed-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The hyperbolic function is a very common function that is widely studied and used in neural networks, filters [18], tracking differentiators [19], etc. Zhang proposed a fuzzy hyperbolic model (FHM) based on hyperbolic tangent [20]- [24], and the analysis showed that the control algorithm has very strong nonlinearity coping ability.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperbolic function is a very common function that is widely studied and used in neural networks, filters [18], tracking differentiators [19], etc. Zhang proposed a fuzzy hyperbolic model (FHM) based on hyperbolic tangent [20]- [24], and the analysis showed that the control algorithm has very strong nonlinearity coping ability.…”
Section: Introductionmentioning
confidence: 99%